Project Based Learning on Creative Economy Competence at Vocational Schools in Bali - Wahjusaputri, Sintha (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aims to analyze the implementation and implementation of industrial working practices (Prakerin) based on project-based blended learning in the field of creative economy expertise at Vocational Schools in Bali Province during the new normal. Industrial work practices (Prakerin) improve students' competence in work experience in the working world industry (IDUKA). The research model uses a qualitative method with a case study. This method is intended to know in depth the implementation of industry work practices (prakterin) based on project based learning online or offline in SMK Bali Province. The research began through direct observation (observation) of the activities of the implementation of industry work practices based on blended learning projects in SmK Bali Province. Data collection techniques are carried out through in-depth interviews with informants who are directly involved in industry work practice activities (prakerin) based on blended learning projects. The research location was conducted at SMKN 1 Sukowati, Bali, SMKN 2 Negara Bali, SMKN 3 Denpasar and SMKN 5 Denpasar Bali Province. The results of this study indicate that: 1) The conditions for implementing project based learning Prakerin are constrained by the limitations of face-to-face learning activities in education units; (2) Project-based, blended learning-based Industrial Work Practice is one solution as a form of student industrial work practice program using online learning as well as face-to-face teaching and collaboration to design, repeat, and complete project-based learning tasks or creative economy products; (3) The industrial work practice curriculum is the result of synchronizing the curriculum in the education unit with the industrial working world curriculum (IDUKA).